Structure–property relations in Cr–C/a-C:H coatings deposited by reactive magnetron sputtering - Gassner, G.; Mayrhofer, P.H.; Mitterer, C.; Kiefer, J. (Surface & coatings technology, 2005)
Amorphous hydrogenated carbon (DLC or a-C:H) coatings have been the subject of intensive research activities within the last two decades due to their superior mechanical and tribological properties. Recently, a nanocomposite concept for severe tribological applications has been proposed, where metal carbides providing enhanced wear resistance are embedded in a lubricating a-C:H matrix. The aim of this work is to investigate coatings based on Cr–C/a-C:H with respect to their structural, mechanical and tribological properties. Coatings in a range of compositions were prepared by reactive unbalanced magnetron (UBM) sputtering from a metallic Cr target in an Ar–CH4 atmosphere. X-ray diffraction and Raman spectroscopy were used to characterize the phase composition of the chromium carbide and a-C:H phases. Dry sliding experiments against different ball counterparts were conducted to determine the friction coefficients. The friction coefficients as well as coating hardness were correlated to different sp3/sp2 a-C:H and chromium carbide fractions within the coatings. The lowest friction coefficients of ∼0.15 could be obtained for coatings deposited at high CH4 partial pressures.